2009
DOI: 10.1016/j.fcr.2008.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Rapid gains in yield and adoption of new maize varieties for complex hillside environments through farmer participation. II. Scaling-up the adoption through community-based seed production (CBSP)

Abstract: Participatory varietal selection (PVS) led to the identification of Population-22 and its later release as Manakamana-3. Subsequently further mother-baby trials tested five unreleased open-pollinated varieties (OPVs), ZM-621, Shitala, Population-45, Hill Pool White, and Hill Pool Yellow to compare them with Manakamana-3. Farmers again preferred Manakamana-3 as well as ZM-621 for their stable, higher grain yield, and for other traits such as stay-green, non-lodging, large white grains, and tolerance to foliar d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The eight locations across the mid-hills were: Fakchhamara of Tehrathum; Thumpakhar of Sindhupalchwok; Kottar of Lalitpur; Maidi of Dhading; Chhatiwan of Palpa; Badamlamji and Bijaura of Dailekh; and Budar of the Doti district. The survey sites stretched from east to west (885 km, 80°4′E to 88°12′E longitude) and north to south (230 km, 30°27′N to 26°22′N latitude) (Tiwari et al 2009b). The HMRP partners have been working with farmers in these locations and distributing seed of new maize varieties for the past 4-5 years or more.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The eight locations across the mid-hills were: Fakchhamara of Tehrathum; Thumpakhar of Sindhupalchwok; Kottar of Lalitpur; Maidi of Dhading; Chhatiwan of Palpa; Badamlamji and Bijaura of Dailekh; and Budar of the Doti district. The survey sites stretched from east to west (885 km, 80°4′E to 88°12′E longitude) and north to south (230 km, 30°27′N to 26°22′N latitude) (Tiwari et al 2009b). The HMRP partners have been working with farmers in these locations and distributing seed of new maize varieties for the past 4-5 years or more.…”
Section: Methodsmentioning
confidence: 99%
“…PVS allowed farmers to evaluate, create awareness and select from a range of improved maize varieties in trials conducted in their own fields, entirely under their own management. Tiwari et al (2009b) also described the effectiveness of communitybased seed production (CBSP) in improving the uptake and adoption of PVS-identified varieties, by enhancing access to seed of new varieties in the remote hillside systems. In this study, we assess the impact of the adoption of improved varieties on increasing the productivity of maize crops of the poor and those with small farms in the midhills areas of Nepal and the extent to which their food security was improved.…”
Section: Introductionmentioning
confidence: 99%
“…Case studies from around the world [85] including Sub-Saharan Africa and Nepal [6,86] have identified a list of functional traits as being important for dry season legume crops including superior drought tolerance and improved biological nitrogen fixation under drought stress [32] (Table 1).…”
Section: Dry Season Wild Plants Can Be Optimized As Cover Crops Throumentioning
confidence: 99%
“…Botanical, agronomic, and anthropological approaches can be combined to understand and improve members of the dry season plant community [10,106,107]. Mother and baby trial designs have been widely adopted in the field of participatory agronomic and plant breeding research with farmers around the world [77,86,108]. Mother trials involve all treatments, while baby trials involve a subset of these treatments including a control [109].…”
Section: Wild Plant Selection Can Benefit From Traditional Knowledge mentioning
confidence: 99%
“…In such regions, there is potential for collective farmer action to promote timely access to seed at affordable prices (Tiwari et al 2009). The seed industry is poorly developed in Timor-Leste, and the formation of seed production groups is one way to improve access to newly identified improved seed, multiply the seed and sell or trade any surplus.…”
Section: Introductionmentioning
confidence: 99%